MUSIC IN INDIAN CULTURE - A. Е. Aksanova (Концепт: философия, религия, культура, 2019)
The article gives an overview of Indian musical art. The author dwells upon history of Indian music, which descends from sacred hymns and songs of ancient India. Music has always been the most important part of Indian life. Religious ceremonies used to play and still play a signifcant role in the life of Indian people. This is the reason why each community has its own musicians and performers of hymns and songs. These songs are mentioned in the most important works of Indian philosophical literature, such as «Rig Veda», «Athharva Veda», «Sama Veda», «Natya Shastra». Music has been an essential part of all Indian holidays since the ancient times till now. With the emergence of Indian theatre the art of singers and musicians comes into high demand. Music has changed with time. However the theory of music and songs presented in ancient books preserved in new forms. Thanks to their careful attitude to classic forms Indian people managed to keep traditions of their music through the centuries. The work presents a classifcation of the music, giving specifc features of classic and folk music. It also brieﬂy presents Indian musical gamma. Ancient Indian music is a synthetic genre which combines singing, dance and music. Indian music is divided into classic and folk music. The classic music is subdivided into northern and southern branches. The author describes complicated classical music gamma which consists of seven notes. There is also a short description of raga in the article. Raga is the basis of Indian classic music. Raga has wide emotional spectrum. It depicts diﬀerent feelings, such as joy, happiness, sadness. According to his desire, a musician choses and creates a rich rhythmical composition. There is also a description of contemporary cinema music and other kinds of modern musical art. An important thing is an unbreakable connection between contemporary and classic music, the preservation of Indian originality in the process of Western inﬂuence.